2017
DOI: 10.1016/j.kint.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

An overview of renal metabolomics

Abstract: The high-throughput, high-resolution phenotyping enabled by metabolomics has been increasingly applied to a variety of questions in nephrology research. This article provides an overview of current metabolomics methodologies and nomenclature, citing specific considerations in sample preparation, metabolite measurement, and data analysis that investigators should understand when examining the literature or designing a study. Further, we review several notable findings that have emerged in the literature that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 67 publications
1
123
1
3
Order By: Relevance
“…As, the endogenous metabolites are the final product of interactions between gene expression, protein expression, and the cellular environment; it provides information that is both complementary to these other molecular domains. Moreover, it also reflects exogenous sources of variation (diet, environment and microbiome) which is meaningful for the study of complex human disease [3]. …”
Section: Introductionmentioning
confidence: 99%
“…As, the endogenous metabolites are the final product of interactions between gene expression, protein expression, and the cellular environment; it provides information that is both complementary to these other molecular domains. Moreover, it also reflects exogenous sources of variation (diet, environment and microbiome) which is meaningful for the study of complex human disease [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Whereas nucleic acids comprise four to five similar chemical motifs, proteins and metabolites span a broad range of size, polarity, and structure, raising considerable analytic challenges. For a detailed review of proteomic and metabolomic methodologies, the reader is referred to other in-depth reviews (15)(16)(17)(18). Mass spectrometry (MS), which differentiates ions-for example peptide fragments or metabolites-on the basis of mass-to-charge ratio, has been a major workhorse for both proteomics and metabolomics.…”
Section: Assay Methodologymentioning
confidence: 99%
“…In this issue of the Journal of the American Society of Nephrology, Tasian et al 2 focused on antibiotic exposures as one explanation for an increasing stone prevalence. In the United States, .250 million courses of antibiotics are prescribed annually to outpatients, 3 with .40 million of these prescribed to children under 18 years of age. 4 A conservative estimate is that 30% of the antibiotics prescribed in the outpatient setting in the United States are unnecessary, with comparable estimates in other developed countries.…”
Section: Does the Receipt Of Antibiotics For Common Infectious Diseasmentioning
confidence: 99%
“…2 Initial metabolomic studies in CKD showed associations between several blood metabolites, eGFR, and future development of CKD. 3,4 Continued technologic improvements, collaborative work across metabolomic platforms, and metabolite profiling in large cohort studies should yield new biomarkers, insights on CKD pathophysiology, and therapeutic opportunities.…”
mentioning
confidence: 99%